The Molecular Basis for Load-Induced Skeletal Muscle Hypertrophy - Marcotte, George R. (Calcif Tissue Int, 2014)
In a mature (weight neutral) animal, an increase in muscle mass only occurs when the muscle is loaded sufficiently to cause an increase in myofibrillar protein balance. A tight relationship between muscle hypertrophy, acute increases in protein balance, and the activity of the mechanistic target of rapamycin complex 1 (mTORC1) was demonstrated 15 years ago. Since then, our understanding of the signals that regulate load-induced hypertrophy has evolved considerably. For example, we now know that mechanical load activates mTORC1 in the same way as growth factors, by moving TSC2 (a primary inhibitor of mTORC1) away from its target (the mTORC activator) Rheb. However, the kinase that phosphorylates and moves TSC2 is different in the two processes. Similarly, we have learned that a distinct pathway exists whereby amino acids activate mTORC1 by moving it to Rheb. While mTORC1 remains at the forefront of load-induced hypertrophy, the importance of other pathways that regulate muscle mass are becoming clearer. Myostatin, is best known for its control of developmental muscle size. However, new mechanisms to explain how loading regulates this process are suggesting that it could play an important role in hypertrophic muscle growth as well. Lastly, new mechanisms are highlighted for how β2 receptor agonists could be involved in load-induced muscle growth and why these agents are being developed as non-exercise-based therapies for muscle atrophy. Overall, the results highlight how studying the mechanism of load-induced skeletal muscle mass is leading the development of pharmaceutical interventions to promote muscle growth in those unwilling or unable to perform resistance exercise.